Analysis of the expression profile and biological function of plasma miRNAs in chronic lymphocytic leukemia and multiple myeloma patients occupationally exposed to pesticides - Luiza Flavia Veiga Francisco; Willian Garcia Birolli; Welinton Hirai; Caroline Rocha Nunes; Iara Zapparoli Gonçalves; Fabiana de Lima Vazquez; Álvaro José dos Santos Neto; Fernando Barbosa Junior; Márcia Maria Chiquitelli Marques; Henrique C.S. Silveira (Ecotoxicology and Environmental Safety)
Acute and chronic exposure to pesticides is associated with several negative effects on human health, such as an increased risk of cancer, including mature B-cell neoplasms such as chronic lymphocytic leukemia (CLL) and multiple myeloma (MM). However, the biological mechanism linking pesticide exposure to the development of CLL and MM has not yet been elucidated. Thus, this study aimed to explore miRNA expression profiles in patients with CLL and MM who were occupationally exposed and not exposed to pesticides. For this purpose, 24 patients with MM and CLL were recruited from a cohort in Brazil and the miRNA expression profiles between the groups were analyzed using Nanostring technology. The study revealed the downregulation of miR-423–3p, miR-1193, miR-576–5p, miR-509–5p, miR-548b-3p, miR-1469, miR-329–3p, and miR-548j-3p, and the upregulation of miR-301b-5p and miR-548ah-5p in patients with CLL and MM were associated with occupational exposure to pesticides. The integrated network analysis of the differentially expressed miRNAs and their target genes in the exposed group demonstrated that miRNAs can participate in the regulation of signaling pathways, such as PI3K/Akt/mTOR and MAPK. Additionally, these miRNAs were found to be associated with an increased risk of developing neurological diseases and various types of cancer. In the present study, we demonstrate, for the first time, altered expression of plasma-derived miRNAs in patients with CLL and MM exposed to pesticides. The plasma miRNAs identified may serve as promising candidates for biomarkers of pesticides effects, potentially contributing to the emerging field of Precision Environmental Health.